2020
DOI: 10.3390/antibiotics9100637
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Biofilm Inhibitory Synergistic Effects of Combinations of Essential Oils and Antibiotics

Abstract: In recent years, the increase of bacteria antibiotic- resistance has been a severe problem for public health. A useful solution could be to join some phytochemicals naturally present in essential oils (EOs) to the existing antibiotics, with the aim to increase their efficacy in therapies. According to in vitro studies, EOs and their components could show such effects. Among them, we studied the activity of Cinnammonum zeylanicum, Mentha piperita, Origanum vulgare, and Thymus vulgaris EOs on bacterial biofilm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 25 publications
(39 reference statements)
2
23
0
Order By: Relevance
“…Our previous studies on EOs showed their synergy with some commercially available antibiotics and demonstrated the effectiveness of these associations by proposing the possibility of a new therapeutic use [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies on EOs showed their synergy with some commercially available antibiotics and demonstrated the effectiveness of these associations by proposing the possibility of a new therapeutic use [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…TEO (Specchiasol Bussolengo, Verona - Italy) composition was determined in three independent experiments using the gas chromatography hyphenated with mass spectrometry (GC-MS) technique, as recently reported ( Rosato et al, 2020 ). Details of sample preparation, instruments and GC-MS analysis methods have been previously reported ( Salvagno et al, 2020 ; Rosato et al, 2018 ).…”
mentioning
confidence: 99%
“…The mixture of PHB powder and PEG after treatment under 150 °C possesses higher antibacterial reduction than each of the individual components. Some antimicrobial agents, such as reactive oxygen species [ 21 ], and radical [ 22 ] and new molecules [ 23 ], may be produced as a result of possible chemical reaction between the mixing components, leading to a better antimicrobial effect than each individual component. To see if this hypothesis was true or false, the mass spectrum (MS) was carried out for the solid and liquid part of mixture of PHB powder and PEG after heat treatment, as well as the individual PHB powder and PEG after heat treatment under 150 °C for 4 h. It can be seen from Figure 4 A that there is no difference between PHB powder and the solid part of mixture of PHB powder and PEG after heat treatment, which means that no new solid antimicrobial component is produced after the reaction of PHB powder and PEG under high temperature.…”
Section: Resultsmentioning
confidence: 99%